Water - Arlon, Penelope (New York : DK, 2006)
Discusses the physical properties and importance of water, including information on the water cycle.
Cover title.
Die-cut cover and fold-out pages.
Includes index.
3.8
K-3
Keywords: Toy and movable books -- Specimens; Water; Toy and movable books